Prognostic factors for tumor recurrence in patients with clinical stage I seminoma undergoing surveillance: a systematic review - Zengerling, Friedemann H.; Jensen, Katrin (Urologic oncology, 2018)
Objective: To systematically evaluate evidence on prognostic factors for tumor recurrence in patients with clinical stage I seminoma undergoing surveillance. Methods: Systematic literature search conducted of Medline, Web of Science, Cochrane Library, and the conference proceedings of the ASCO, AUA, and EAU meetings (last search: October 2016), according to our prospectively registered protocol (PROSPERO registration number CRD42014009434). Identified records were reviewed according to the Cochrane Method Group of Prognosis Reviews recommendations and the PRISMA reporting guideline. Study quality was appraised with the Quality in Prognosis Studies (QUIPS) tool. Results: Nineteen studies reporting on 26 potential prognostic factors were included in our analysis. Among the most frequently reported factors, tumor size (continuous or dichotomized) was significantly associated with relapse in 10/14 studies with a hazard ratio (HR) ranging from 1.33 (95% confidence interval [CI]: 1.14-1.56) to 3.17 (95% CI: 1.08-9.26). Rete testis invasion was significantly associated with relapse in only 4/13 studies with a HR ranging from 1.18 (95% CI: 0.92-1.51) to 1.36 (95% CI: 0.81-2.28). Lymphovascular invasion, young age, and preoperative HCG level had no association with relapse. Our findings are limited by heterogeneity of study designs, potential reporting bias, and moderate-to-poor study quality. Conclusion: In stage I seminoma, tumor size is the most valuable prognostic factor on which to base relapse risk and to counsel patients about adjuvant treatment. Large tumor size was defined quite inhomogenously among the included studies, so no distinct cutoff value for tumor size can be recommended. Other potential prognostic factors including rete testis invasion play a minor role in stage I seminoma.